2005
DOI: 10.1111/j.1471-0528.2004.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Previous induced abortions and the risk of very preterm delivery: results of the EPIPAGE study

Abstract: Members of the EPIPAGE Group are listed on AppendixObjectives To evaluate the risk of very preterm birth (22 -32 weeks of gestation) associated with previous induced abortion according to the complications leading to very preterm delivery in singletons. Design Multicentre, case-control study (the French EPIPAGE study).Setting Regionally defined population of births in France.Sample The sample consisted of 1943 very preterm live-born singletons (<33 weeks of gestation), 276 moderate preterm live-born singletons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
43
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 34 publications
10
43
3
2
Order By: Relevance
“…In present study, highest number of participants were belonged to age group of 20 to 25 years and these findings are correlated with the similar study done by Annapurma P et al 12 Parity, pregnancy outcome observations were also comparable with the similar study done by Annapurna P et al, Zhou W et al and Moreau C et al [12][13][14] Present study observed low birth weight in 19.9% cases who had a history of abortion and this findings are not correlate with the similar study done by Annapurna P et al and Basso O et al [12][13][14][15] Present results show that any pregnancy following an initial miscarriage is associated with a degree of increased obstetric and perinatal risk. This study questions the evidence behind the attribution of risk only to women who have had three or more consequent miscarriages (recurrent miscarriage).…”
Section: Discussionsupporting
confidence: 91%
“…In present study, highest number of participants were belonged to age group of 20 to 25 years and these findings are correlated with the similar study done by Annapurma P et al 12 Parity, pregnancy outcome observations were also comparable with the similar study done by Annapurna P et al, Zhou W et al and Moreau C et al [12][13][14] Present study observed low birth weight in 19.9% cases who had a history of abortion and this findings are not correlate with the similar study done by Annapurna P et al and Basso O et al [12][13][14][15] Present results show that any pregnancy following an initial miscarriage is associated with a degree of increased obstetric and perinatal risk. This study questions the evidence behind the attribution of risk only to women who have had three or more consequent miscarriages (recurrent miscarriage).…”
Section: Discussionsupporting
confidence: 91%
“…3,5 Moreau C et al concluded that previous history of induced increased abortions is associated with preterm births. 7 In present study infections both vaginal and urinary were seen to be strongly associated with preterm delivery, 19% of cases had vaginal infection and 15% had urinary tract infections. Genitourinary infections has been reported to be one of the commonest risk factors in literature, Wright SP et al identified urinary tract infection (UTI) in 7% of preterm births.…”
Section: Discussionmentioning
confidence: 83%
“…Contrary to common belief, population-based studies [34][35][36] have found that elective pregnancy terminations in the first and second trimesters are associated with a very small but apparently real increase in the risk of subsequent spontaneous preterm birth (PTB). 37 The mechanism is unknown.…”
Section: Identification Of Women With a Prior Preterm Birthmentioning
confidence: 93%